Answer:
Given :
→x-y=12
→xy= 3²
=9
Equation formed:
![{(x - y)}^{2} = {x}^{2} + {y}^{2} - 2xy](https://tex.z-dn.net/?f=%20%7B%28x%20-%20y%29%7D%5E%7B2%7D%20%20%3D%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%20-%202xy)
Step by step explanation:
![{(12)}^{2} = {x}^{2} + {y}^{2} - 2 \times 9 \\ 144 + 18 = {x}^{2} + {y}^{2} \\ = 162](https://tex.z-dn.net/?f=%20%7B%2812%29%7D%5E%7B2%7D%20%20%3D%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%20-%202%20%5Ctimes%209%20%5C%5C%20%20144%20%20%20%2B%2018%20%3D%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%20%5C%5C%20%20%3D%20162)
hope it helped you:)
Hi!
So really focus on the fact that he started at $230, and then added an amount of money which we'll call x, which made his total equal $599.
Take the parts I put in bold, and write the equation.
$230 + x = $599
Now we need to find x.
Whatever we do to the equation, we do it to both sides.
Our goal is to isolate x on one side.
Subtract 230 from both sides.
$230 - $230 + x = $599 - $230
x = $369
The answer is A. $230 + x = $599 x = $369
Hope this helps! :)
-Peredhel
Answer:
![(\frac{dy}{dt})^2=sin^2t](https://tex.z-dn.net/?f=%28%5Cfrac%7Bdy%7D%7Bdt%7D%29%5E2%3Dsin%5E2t)
Step-by-step explanation:
![y=cost](https://tex.z-dn.net/?f=y%3Dcost)
DE :![(\frac{dy}{dt})^2=1-y^2](https://tex.z-dn.net/?f=%28%5Cfrac%7Bdy%7D%7Bdt%7D%29%5E2%3D1-y%5E2)
If y is a solution of given DE then it satisfied the DE.
Differentiate w.r.t t
![\frac{dy}{dt}=-sint](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdt%7D%3D-sint)
Using the formula
![\frac{d(cosx)}{dx}=-sinx](https://tex.z-dn.net/?f=%5Cfrac%7Bd%28cosx%29%7D%7Bdx%7D%3D-sinx)
LHS:![(\frac{dy}{dt})^2=(-sint)^2=sin^2t](https://tex.z-dn.net/?f=%28%5Cfrac%7Bdy%7D%7Bdt%7D%29%5E2%3D%28-sint%29%5E2%3Dsin%5E2t)
RHS
![1-y^2=1-cos^2t=sin^2t](https://tex.z-dn.net/?f=1-y%5E2%3D1-cos%5E2t%3Dsin%5E2t)
By using the formula
![sin^2t=1-cos^2t](https://tex.z-dn.net/?f=sin%5E2t%3D1-cos%5E2t)
LHS=RHs
Hence, y is a solution of given DE
![(\frac{dy}{dt})^2=sin^2t](https://tex.z-dn.net/?f=%28%5Cfrac%7Bdy%7D%7Bdt%7D%29%5E2%3Dsin%5E2t)
Answer:
x=3
Step-by-step explanation:
3x+5=14
-5 -5
3x=9
/3 /3
x=3
Simplified: -6m-6
Factored: 6(m+1)